The Study of Cost and Quality of New York School Districts. Final Report - Kiesling, Herbert J.; Indiana Univ., Bloomington ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This is a study of the relationship of a number of school and community characteristics to achievement performance levels of fifth and eighth grade pupils in a 1965 sample of 99 school districts (86 usable) in New York state. A simple model of the educational process was constructed and the relative importance of a number of school inputs compared. Units of observation used were both schools and school districts. Results were compared to a similar study of an earlier (1958) sample of New York school districts. The key findings of the investigation are listed. Tables are included. (Author/LS)
Contract Number: OEG-0-8-080264-3732(085).
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cost Effectiveness; Elementary Schools; School Districts; Achievement Rating; Community Characteristics; Performance Factors; Statistical Analysis; New York